Using PIRLS and TIMSS data for the assessment of efficiency and effectiveness of primary education in post-socialist and old democracy EU member states - Stumbrienė, Dovilė; Želvys, Rimantas; Žilinskas, Julius; Jakaitienė, Audronė (Lithuanian Journal of Statistics, 2022)
It is a data-oriented approach to evaluate the performance of a set of decision-making units in the process of transforming resources (inputs) into desired results (outputs). The input indicators are the education expenditure and student/teacher ratio; the output indicators are the standard deviations of scores and percentage of resilient students. The standard deviation of the scores can explain how skills and knowledge are distributed throughout the student population, and the percentage of resilient students indicates to what extent the socioeconomic background precludes or does not preclude student success.